KUALITAS LAYANAN WEBSITE PERPUSTAKAAN PERGURUAN TINGGI DI LAMPUNG MENGGUNAKAN METODE WEBQUAL MODIFIKASIAN DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Ridzana Wulantika; Tristiyanto Tristiyanto; Yunda Heningtyas (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
Library website is used as a searching platform of literature information for easier and faster usage. This study aims to evaluate of website services using modified webqual and IPA methods. The library website that will be evaluated are the website of the University of Lampung (Unila) library, Lampung State Islamic University (UIN), Sumatra Institute of Technology (ITERA), Lampung State Polytechnic (Polinela) and Malahayati University (Unmal). Total of analyzed respondents was 219. Data analysis methods used in this study was structural equation models (SEM) with the Partial Least Square (PLS) approach. The result shows that the interaction quality and empathy gives a great influence to student’s satisfaction. In addition, the results of the Importance Performance Analysis (IPA) test result found user friendly website attributes, password and contact person availability, service satisfaction, administrator's response, hospitality and patience influencing to student’s satisfaction in Unila, UIN, Itera, Polinela and Unmal.